Modeling of the controlled release of betacarotene into anhydrous ethanol from microcapsules - Jucelio Kilinski Tavares; Antônio Augusto Ulson de Souza; José Vladimir de Oliveira; Wagner Luiz Priamo; Selene M.A. Guelli Ulson de Souza (Elsevier, 2016)
In this paper several models of the mass transfer process are described with the aim of simulating the release of active principles from matrix-type polymeric microcapsules. The following mathematical models, which are available in the literature, are applied in this study: Fick's second law (CDMASSA), the linear drive force (LDF), an analytical model and other semi-empirical models. The release of the active principle (betacarotene) contained in microcapsules (PHBV) into a solvent (ethanol) was investigated. It was observed that the model obtained with Fick's second law provided a better fit with the literature data compared with the LDF model, the analytical model and the semi-empirical models. It can be concluded from this finding that the most complete model, based on the phenomenology of the problem, provided the best result.